2016
DOI: 10.1002/bjs.10326
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of sacral nerve stimulation for refractory constipation

Abstract: These results do not support the recommendation of permanent implantation of a pulse generator in patients with refractory constipation who initially responded to temporary nerve stimulation. Registration number: NCT01629303 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 24 publications
1
74
0
2
Order By: Relevance
“…Recent randomized double-blind crossover studies have shown no difference between active and sham stimulations [17, 19]. In both studies, 30–60% of patients had a positive response during sham stimulation, suggestive of either lasting effects of sensory stimulation beyond washout period between sham and active treatment (2–3 weeks) or high placebo effects of this treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Recent randomized double-blind crossover studies have shown no difference between active and sham stimulations [17, 19]. In both studies, 30–60% of patients had a positive response during sham stimulation, suggestive of either lasting effects of sensory stimulation beyond washout period between sham and active treatment (2–3 weeks) or high placebo effects of this treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Early studies on SNM for functional constipation were encouraging with both subjective and objective evidence of a positive treatment effect . However, two double‐blinded, placebo‐controlled studies have failed to show any significant change in their primary endpoint . Furthermore, in a consecutive follow‐up study by Dinning et al the explantation rate of 92%, mostly due to a lack of treatment effect, was extremely high .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to recognize that although SNS has become an established treatment option for adults with refractory fecal incontinence, evidence for its use for adults with constipation is less clear . In fact, two recent randomized crossover studies did not find SNS to be more effective than sham stimulation for adults with refractory constipation . In children, fecal incontinence often occurs secondary to poorly controlled constipation and is commonly used as a primary outcome to define treatment success in studies of pediatric constipation .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, experience with the use of SNS to treat adults with constipation and fecal incontinence has grown, and SNS is now considered the first‐line surgical treatment for adults with fecal incontinence refractory to conventional treatment . However, recent studies have not shown SNS to be an effective treatment for adults with constipation . Experience with the use of SNS in children with constipation has been positive thus far but remains limited, and the long‐term outcomes of SNS treatment in children with constipation are not yet clearly understood .…”
Section: Introductionmentioning
confidence: 99%